Facile Synthesis of 3-Thio-Substituted 9-Oxo-1-Hetaryl-9H-Indeno[2,1-c]Pyridine-4-Carbonitriles as End Groups for Non-Fullerene Acceptors - Usova, Sofia D.; Knysh, Margarita I.; Knyazeva, Ekaterina A.; Mikhalchenko, Ludmila V.; Rakitin, Oleg Alekseevich (Synthesis, 2025)
We developed mild synthetic conditions for the formation of 3-thio-substituted 9-oxo-1-hetaryl-9H-indeno[2,1-c]pyridine-4-carbonitriles in quantitative yields via the reaction of readily available 2-(3-oxo-2-arylidene-2,3-dihydro-1H-inden-1-ylidene)malononitrile with S-nucleophiles. The developed protocol demonstrated superior efficiency to N-nucleophiles via a two-step approach compared to the known methods. The potential application of the synthesized thio-substituted 2-azafluorenones as terminal groups in non-fullerene acceptors (NFAs) for organic solar cells was successfully demonstrated. The key characteristics of these novel end-group-functionalized NFAs were evaluated and compared with well-established literature analogs.
Keywords: 2-Azafluorenones; S-Nucleophiles; 2-(3-Oxo-2-arylidene-2,3-dihydro-1H-inden-1-ylidene)malononitrile; Non-fullerene acceptors; Organic solar cells